ANALISIS SUMBER-SUMBER AIR PADA DAERAH ALIRAN SUNGAI (DAS) KARAJAE DALAM MENUNJANG KETERSEDIAN AIR BAKU KOTA PARE-PARE - Mulyadi Mulyadi (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2019)
This study aims to (1) Determine land cover in the Karajae watershed area. (2) Identifying the Location of Water Sources through Soil Analysis of Water Assessment Tools (SWAT). (3) Make a map describing the unit of land available and the location of the water source in the Karajae watershed. This research was conduct in the Karajae Watershed from July to September 2017.  Primary data is obtained directly through the interpretation of satellite imagery to make land cover maps. Retrieval of data on land cover in the field doing by adjusting the classification of land cover in the field with the results of the interpretation of satellite imagery purposively base on accessibility. Secondary data is data covering the general condition of the research location obtained from the study of literature and other data related to research. The secondary data includes the DAS Boundary Map, River Network Map, DEM 30m Aster, 2016 Land Closure Map, Soil Type Map, Climate Data. This study used the SWAT model. The results obtained from this study are the 2016 Landsat Image Interpretation Results 2016 and the Karajae watershed field check results. There are 11 types of land cover which are dominated by dryland agriculture with a percentage of land area of 35.1% followed by shrubland cover with an area of 17.0% and bush mixed dryland agriculture with a percentage of the area of 12.5% and low-density dryland forest with a percentage of the area by 12.2%. Land cover has the smallest percentage of area, namely ponds by 0.2%. The results of SWAT analysis identification obtained 17 sub-watersheds as water sources that have high water availability, spread in three districts, namely Sidenreng Rappang, Barru District and Pare-Pare City. The results of the classification of water availability values in 17 sub-watersheds that have high water availability values, namely the western Bacukiki sub-watershed, located in the City of Pare-pare where the sub-watershed covers 4 villages namely new Bojo, Bumi Harapan, Lumpue, Wattang Bacukiki with the availability value water of 133,952,197.80 m3.